2021
DOI: 10.1002/adma.202100714
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Poly(3‐hexylthiophene) as a Conductivity‐Reducing Additive for Polyethylene‐Based High‐Voltage Insulation

Abstract: Poly(3‐hexylthiophene) (P3HT) is found to be a highly effective conductivity‐reducing additive for low‐density polyethylene (LDPE), which introduces a new application area to the field of conjugated polymers. Additives that reduce the direct‐current (DC) electrical conductivity of an insulation material at high electric fields have gained a lot of research interest because they may facilitate the design of more efficient high‐voltage direct‐current power cables. An ultralow concentration of regio‐regular P3HT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The activation energy of the epoxy composite (0.9 eV) is lower than that of pure epoxy (1.20 eV) at a high temperature. The mobility of polymer molecular chains at the interface area in the composite is inhibited due to the steric hindrance effect of nano− and micro fillers, which equally introduces deep trapping sites at the interface area; thus, ionic charge transport in the composite is suppressed compared to the pure polymer [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The activation energy of the epoxy composite (0.9 eV) is lower than that of pure epoxy (1.20 eV) at a high temperature. The mobility of polymer molecular chains at the interface area in the composite is inhibited due to the steric hindrance effect of nano− and micro fillers, which equally introduces deep trapping sites at the interface area; thus, ionic charge transport in the composite is suppressed compared to the pure polymer [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…9 Pourrahimi et al found that the electrical conductivity of the LDPE decreased by three times by adding an extremely low content of poly-3 hexylthiophene (P3HT), which is the highest reduction reported so far. 10 Jarvid et al explored the influence of alkyl side chain length on the electrical tree suppression of different benzoyl-based voltage stabilizers and found that the shortest side chain had the strongest effect. 11 Adding different aromatic compounds into XLPE showed that voltage stabilizers with high electron affinity can significantly inhibit space charge injection 12,13 and electrical tree inception.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al found that the DC breakdown strength of XLPE can be improved at different temperatures by grafting aromatic ketone compounds due to latters' excellent quantum chemical properties 9 . Pourrahimi et al found that the electrical conductivity of the LDPE decreased by three times by adding an extremely low content of poly‐3 hexylthiophene (P3HT), which is the highest reduction reported so far 10 . Jarvid et al explored the influence of alkyl side chain length on the electrical tree suppression of different benzoyl‐based voltage stabilizers and found that the shortest side chain had the strongest effect 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have enhanced the breakdown field strength, by introducing nanoparticles into polymers through physical blending or chemical deposition, [7][8][9][10][11][12] multicomponent organic material blending, [13] and magnetron sputtering coating. [14] These have improved the electrical properties of materials to some extent and achieved landmark achievements.…”
Section: Introductionmentioning
confidence: 99%